Genomic landscape and expression profile of consensus molecular subtype four of colorectal cancer - Lu, Yujie; Gu, Dingyi; Zhao, Chenyi; Sun, Ying; Li, Wenjing; He, Lulu; Wang, Xiaoyan; Kou, Zhongyang; Su, Jiang; Guo, Feng (Frontiers in Immunology, 2023)
Background: Compared to other subtypes, the CMS4 subtype is associated with lacking of effective treatments and poorer survival rates. Methods: A total of 24 patients with CRC were included in this study. DNA and RNA sequencing were performed to acquire somatic mutations and gene expression, respectively. MATH was used to quantify intratumoral heterogeneity. PPI and survival analyses were performed to identify hub DEGs. Reactome and KEGG analyses were performed to analyze the pathways of mutated or DEGs. Single-sample gene set enrichment analysis and Xcell were used to categorize the infiltration of immune cells. Results: The CMS4 patients had a poorer PFS than CMS2/3. CTNNB1 and CCNE1 were common mutated genes in the CMS4 subtype, which were enriched in Wnt and cell cycle signaling pathways, respectively. The MATH score of CMS4 subtype was lower. SLC17A6 was a hub DEG. M2 macrophages were more infiltrated in the tumor microenvironment of CMS4 subtype. The CMS4 subtype tended to have an immunosuppressive microenvironment. Conclusion: This study suggested new perspectives for exploring therapeutic strategies for the CMS4 subtype CRC.